2017
DOI: 10.1016/j.jvs.2016.08.092
|View full text |Cite
|
Sign up to set email alerts
|

Midterm results of the fenestrated Anaconda endograft for short-neck infrarenal and juxtarenal abdominal aortic aneurysm repair

Abstract: The fenestrated Anaconda is a viable treatment option for complex abdominal aortic aneurysms. Acceptable mortality and morbidity and low reintervention rates contribute to good midterm results. Occurrence of early type I endoleak was relatively common, but these resolved spontaneously in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The primary outcomes were 30-day/in-hospital mortality and postoperative renal insufficiency. Secondary outcomes Wooster et al 16 Blankensteijn et al 12 Katsargyris et al 20 Caradu et al 7 Saratzis et al 22 Vemuri et al 13 Kristmundsson et al 14 Grimme et al 15 Banno et al 17 Oderich et al 23 Perot et al 18 Manning et al 21 Total 0 0…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcomes were 30-day/in-hospital mortality and postoperative renal insufficiency. Secondary outcomes Wooster et al 16 Blankensteijn et al 12 Katsargyris et al 20 Caradu et al 7 Saratzis et al 22 Vemuri et al 13 Kristmundsson et al 14 Grimme et al 15 Banno et al 17 Oderich et al 23 Perot et al 18 Manning et al 21 Total 0 0…”
Section: Discussionmentioning
confidence: 99%
“…Despite the early advantages of the endovascular approach, secondary reinterventions remain high with FEVAR, averaging 22% to 37% at 5 years in recent reports. [15][16][17][18][19] Tinelli et al 20 reported a retrospective propensity matched comparison of FEVAR with open surgical repair. In that study, open surgical repair had higher rates of acute kidney injury (52% vs 20%), similar freedom from renal function deterioration, but higher freedom from reinterventions at 6 years (93.4% vs 63.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Primary treatment was shown to have an early complication rate of 19% to 24%. [20][21][22][23] Postoperative complication risk and mortality require limitation of the use of the Fenestrated Anaconda cuff to patients in whom open repair is not an option, and careful selection of patients is essential.…”
Section: Discussionmentioning
confidence: 99%